Understanding and Managing Tourism Impacts : an Integrated Approach. - Hall, C. Michael Michael (Contemporary geographies of leisure, tourism, and mobility., 2012)
As one of the world's largest industries, tourism carries with it significant social, environmental, economic and political impacts. Although tourism can provide significant economic benefits for some destinations, the image of tourism as a benign and environmentally friendly industry has often been challenged. There is a clear and growing body of evidence that suggests that the effects of tourism development are far more complex than policy-makers usually suggest and that the impacts of tourism occur not just at the destination but at all stages of a tourist's trip. Furthermore, tourism do.